Antioxidant activities, proteolytic activity and growth behavior of Lactobacillus cultures during fermentation of goat milk - Panchal, Gauravkumar; Hati, Subrota Hati; Darji, V B; Prajapati, J B (Indian Journal of Dairy Science, 2020)
In the study, five Lactobacillus cultures i.e. Lb. fermentum (M3), Lb. casei (NK9), Lb. rhamnosus (M8), Lb. rhamnosus (M9) and Lb. paracasei (M11) were used for the fermentation of goat milk. Lactobacillus cultures were evaluated for their growth behavior on pH, acidity and Lactobacillus counts for different time periods. We found that pH reduction by Lactobacillus cultures in goat milk medium was ranged from pH 6.25 at 0 h to pH 3.06 after 48h at 37ºC, for acidity produced by Lactobacillus cultures was ranged from 0.28 in 0 h to 3.21%LA after 48 h at 37ºC and for lactic counts (log CFU/ml) were ranged from 3.87 log CFU/ml at 0 h to 9.03 log CFU/ml after 36 h incubation at 37ºC. Then, antioxidant activities (ABTS assay, Hydroxyl free radical scavenging assay and Superoxide free radical scavenging assay) as well as proteolytic activity (OPA method) were analyzed for different time periods and found that antioxidant activity (ABTS assay) of Lactobacillus cultures was in the range of 42.14 to 53.27%, hydroxyl free radical scavenging activity of Lactobacillus cultures was found in the range of 35.32 to 53.43%, superoxide free radical scavenging activity of Lactobacillus cultures was in the range of 24.34% to 50.99% and proteolytic (OPA) activity of Lactobacillus cultures was found in the range of 7.30 to 9.96 mg/ml.